Endoscopic treatment of sporadic small duodenal and ampullary neuroendocrine tumors - Gincul, Rodica; Ponchon, Thierry; Napoleon, Bertrand; Scoazec, Jean-Yves; Guillaud, Olivier; Saurin, Jean-Christophe; Ciocirlan, Mihai; Lepilliez, Vincent; Pioche, Mathieu; Lefort, Christine; Adham, Mustapha; Pialat, Jean; Chayvialle, Jean-Alain; Walter, Thomas (Endoscopy, 2016)
Background and study aim: As duodenal neuroendocrine tumors (NETs) are rare, their optimal management has not been clearly established. The aim of this study was to evaluate the feasibility and outcome of endoscopic treatment of duodenal NETs. Patients and methods: We reviewed the files of all patients who underwent endoscopic resection of a sporadic duodenal or ampullary NET between 1996 and 2014 at two centers. Results: A total of 29 patients with 32 uT1N0M0 NETs < 20 mm were included. Treatment consisted of endoscopic mucosal resection in 19 cases, and cap aspiration in 13 cases. Prior submucosal saline injection was used in 15 cases. Mortality was 3 % (one severe bleeding). Morbidity was 38 % (11/29). At post-resection analysis, mean tumor size was 8.9 mm (range 3 – 17 mm), 29 lesions were stage pT1, one was pT2, and 2 were pTx because of piecemeal resection. All NETs were well differentiated. A total of 27 lesions were classified as grade 1 and 5 were grade 2. The resection was R0, R1, and Rx for 16, 14, and 2 lesions, respectively. Three R1 patients underwent additional surgical treatment, with no residual tumor on the surgical specimen but with positive metastatic lymph nodes in two cases. One patient was lost to follow-up. Finally, 24 patients were included in the follow-up analysis. The median follow-up period was 56 months (range 6 – 175 months). Two patients presented a tumor recurrence during the follow-up period.Conclusions: Endoscopic treatment of small duodenal NETs was associated with significant morbidity, a difficulty in obtaining an R0 specimen, and the risk of lymph node metastasis. Nevertheless, it represents an interesting alternative in small grade 1 duodenal lesions and in patients at high surgical risk.